Enteric methane emissions, rumen fermentation, and milk composition of dairy cows fed 3-nitrooxypropanol and L-malate supplements - Zhou, Xiaokang; Fu, Shuaiqi; Li, Gaiying; Yao, Zhaohui; Du, Xingjie; Zhang, Yan; Gao, Tengyun (Frontiers in Veterinary Science, 2024)
Twenty-four cows were used in a randomized complete block design. Cows were assigned to three groups: (1) Control, (2) 3-nitrooxypropanol (NOP) of 200 mg/kg feed dry matter (10% NOP), and (3) NOP × MAL (10% NOP at 200 mg/kg feed dry matter plus 99% L-malate at 10 g/kg feed dry matter). Cows were fed for 10-wk. NOP did not affect dry matter intake (DMI) or milk yield, whereas NOP × MAL decreased DMI but did not affect milk yield. Average methane production decreased by 54% in NOP and by 51% in NOP × MAL. Both NOP and NOP × MAL increased concentrations of milk fat and protein. In addition, concentrations of short-chain fatty acids and total saturated fatty acids increased in both NOP and NOP × MAL. However, total monounsaturated fatty acids and total polyunsaturated fatty acids only increased in NOP × MAL.